The Ediacaran paleontological record in South America - Warren, Lucas V. [UNESP]; Berker-Kerber, Bruno; Inglez, Lucas [UNESP]; Varejão, Filipe G.; Morais, Luana P.C. [UNESP]; Simões, Marcello G. [UNESP]; Freitas, Bernardo T.; Arrouy, Julia M.; Gómez-Peral, Lucía E.; Poiré, Daniel G.; Okubo, Juliana [UNESP]; Caxito, Fabrício; et al. (My University, 2024)
South America figures as one of the most fruitful continents for paleontological research on the Ediacaran-Cambrian transition, with almost 100 years of studies on organisms preserved in carbonates and siliciclastic successions deposited during the birth of the Gondwana supercontinent. However, this scientific record is often scattered among local publications which is part of the reason for the unfamiliarity of geoscientists with the Ediacaran paleontology of this continent. To address this issue, this paper provides a comprehensive overview of Ediacaran paleontology in South America. It achieves this by conducting a thorough assessment of existing research alongside presenting ample new data concerning fossil discoveries. Following current efforts to add new pieces to the complex puzzle on metazoan evolution, this contribution resumes our understanding of the variety and diversity of Ediacaran assemblages in this part of the planet. Positioning South American successions in space and time and comparing them with occurrences worldwide helps us understand the different pulses of extinctions, and their forcings and consequences for life diversification during the Ediacaran. Lastly, by definitively adding the paleontological record of SW Gondwana to the global picture, we seek to contribute to current discussions on the subdivision of the Ediacaran, perhaps the most emblematic period in the geological record.
Keywords: Biostratigraphy; Historical paleontology; Late Ediacaran microfossils; MISS; Nama-style preservation; Simple and complex trace fossils; Skeletal Ediacaran organisms; South America